2004
DOI: 10.1007/s00268-003-6903-1
|View full text |Cite
|
Sign up to set email alerts
|

Complications of Thyroid Surgery: Analysis of a Multicentric Study on 14,934 Patients Operated on in Italy over 5 Years

Abstract: Complication rates associated with thyroid surgery can be evaluated only through analysis of case studies and follow-up data. This study covers postoperative data from 14,934 patients subjected to a follow-up of 5 years. Among them, 3130 (20.9%) underwent total lobectomy (TL), 9599 (64.3%) total thyroidectomy (TT), 1448 (9.7%) subtotal thyroidectomy with a monolateral remnant (MRST), and 757 (5.1%) subtotal thyroidectomy with bilateral remnants (BRST). A total of 6% of the patients had already been operated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

35
586
13
40

Year Published

2006
2006
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 786 publications
(674 citation statements)
references
References 19 publications
35
586
13
40
Order By: Relevance
“…In a study by Thomusch et al more extensive surgery increased the relative risk of permanent hypocalcemia by 1.5-1.8 times [6]. However, in some other studies, it was concluded that more radical surgery did not result in higher rates of hypoparathyroidism [10,11]. In our study, when subtotal thyroidectomy was compared with total thyroidectomy, the extent of the surgery did not increase the permanent hypocalcemia rates.…”
Section: Discussioncontrasting
confidence: 59%
“…In a study by Thomusch et al more extensive surgery increased the relative risk of permanent hypocalcemia by 1.5-1.8 times [6]. However, in some other studies, it was concluded that more radical surgery did not result in higher rates of hypoparathyroidism [10,11]. In our study, when subtotal thyroidectomy was compared with total thyroidectomy, the extent of the surgery did not increase the permanent hypocalcemia rates.…”
Section: Discussioncontrasting
confidence: 59%
“…They manifest as a lowered voice tone, vocal fatigue and difficulty in singing note intonation [25].…”
Section: Discussionmentioning
confidence: 99%
“…Partial/total thyroid surgery has so far constituted the only therapeutic approach for these. Although surgery is widely available, highly effective, and safe in skilled centers, complications (both temporary and permanent) still occur in 2-10 % of cases [5,6]. Hypothyroidism is an unavoidable effect after total thyroidectomy, requiring lifelong L-thyroxine replacement therapy.…”
Section: Introductionmentioning
confidence: 99%